TASK – BASED LEARNING: DESIGN AND IMPLEMENTATION IN TEACHING ENGLISH FOR VARIOUS SCIENTIFIC DISCIPLINE STUDENTS IN A LARGE CLASS - Umi Sholihah; Kunthum Ria Anggraheny (Akademika, 2023)
It is a Classroom Action Research with the aim to describe the implementation of Task-Based Learning for students of various scientific disciplines in large class to improve students’ English ability. This research subjects were first semester students at Widya Dharma University Klaten in the general course (MKU) of English in group F with a total number of students are 103. The technique of collecting the data were test, observation, interview, and documentation. This research conducted in two cycles with a posttest in every cycle. The results found that there were the improvement of students’ English skills based on the mean scores of post-test in cycles 1 and 2 in Informatics Engineering class A was from 72 to 75, class B was from 76 to 79, Informatics Management was from 73 to 80, Geography Education was from 60 to 77, Civic Education was from 65 to 77, Physiotherapy was from 70 to 76, and Agricultural Product Technology had same score was 78. From the observation, activities in Task - Based learning trained students’ cooperative attitude, improved their interest, and enriched English vocabularies on their own scientific disciplines. This research can be as a reference for teachers in large class to create innovative activities to achieve learning goals; as source of information and reference material for further research to be further developed in other materials to improve the quality of learning.